Subalar cutaneous cysts with Harpirhynchus nidulans in bearded tits and hawfinches in Central Europe - Literák, Ivan; Chytil, Josef; Trnka, Alfréd; Fain, Alex; Tukac, Viktor (Avian pathology, 2005)
In wild bearded tits (Panurus biarmicus) and hawfinches (Coccothraustes coccothraustes) trapped in the Czech Republic and Slovakia from 1999 to 2003, characteristic yellow thin-walled subalar cutaneous cysts filled with friable material containing mites Harpirhynchus nidulans were found. The biggest cysts were 14 mm and 20 mm in size in bearded tits and in hawfinches, respectively. Histologically, the relatively thick wall of cysts contained erythrocytes (extravased or in small vessels) and heterophils; mononuclear cells were not found. The prevalences of subalar cysts in bearded tits at Nesyt (Czech Republic), Pusté Ul'any (Slovakia) and Parizské Mociare (Slovakia) were 6.1% (11 positive/180 examined), 12.7% (13/102) and 4.2% (4/96), respectively. The overall prevalence of subalar cutaneous cysts in bearded tits was 7.4% (28/378). The cutaneous cysts were found on adult birds only. Subalar cysts of H. nidulans in hawfinches were also found in four other locations in the Czech Republic and Slovakia.
Keywords: Animals; Česká republika; infestace roztoči; Passeriformes; Bird Diseases; Slovenská republika; Cysts; Mite Infestations; zvířata; Slovakia; nemoci ptáků; Czech Republic; cysty